Occupational health Analysis in dentists of Tehran - P. Nasiri; F Golbabaie; M. Mahmodi (Tehran University of Medical Sciences, 1993)
In order to evaluate occupational health in dentists of Tehran, 250 dentists ( 60f/190m) were selected. The results of our survey showed significant hearing loss in both ears of all the dentists mostly in 6 ghz frequencies. Urine analysis showed higher mercury levels in general practitioners than specialists Although this was not statistically significant. The majority of dentists refused to reply questions about occupational diseases. Only the younger generation of them with working experience of 5-9 years replied to all the questions of questionnaire.